Post Decentralization Corruption: A study on perpetual corruption at the local level in West Lombok - Iwan Tanjung Sutarna; Subando Agus Margono; Agus Heruanto Hadna (Policy & Governance Review, 2021)
The current article aims to explore corruption at the local level. There are two main discourses that set the background for this study. First, corruption is considered a result of decentralization, which opened up the local political structure. Second, corruption happened as a result of a societal shift along the prismatic continuum. These two main discourses serve as the theoretical background in research to find the meanings behind the reality of perpetual corruption occurring at the local level. The research employed the theory of decentralization and a prismatic society approach as analytical tools along with a phenomenological approach. The study found linkages in decentralization as a new reason for the growth and development of corruption at the local level on account of the prismatic structure empowering elite rulers to replicate corrupt practices.